2022
DOI: 10.18502/kss.v0i0.12318
|View full text |Cite
|
Sign up to set email alerts
|

Managing the 8 Wastes of Lean at a Higher Education Institution: An ISM-MICMAC Approach

Abstract: A Higher Education Institution (HEI) is required to be more competitive in maintaining its sustainability. The large number of stakeholders of an HEI makes it difficult to be agile in the intense competition. One of the concepts that can be used to improve the agility of an HEI is the Lean philosophy. Lean philosophy focuses on eliminating waste in the process of creating value for stakeholders. Previous research has identified several wastes in the operational activities of an HEI. This study aimed to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In this study, an analysis of the driving and dependence powers of challenges permitted the decision-makers to develop a framework that can be used by policymakers and stakeholders in India's education sector. Hartanti et al (2022) also used ISM-MICMAC to model the relationship of the eight identified lean wastes in higher education institutions. Through the development of the model, a more effective prioritization was developed in the formulation of a series of actions to eliminate the waste.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, an analysis of the driving and dependence powers of challenges permitted the decision-makers to develop a framework that can be used by policymakers and stakeholders in India's education sector. Hartanti et al (2022) also used ISM-MICMAC to model the relationship of the eight identified lean wastes in higher education institutions. Through the development of the model, a more effective prioritization was developed in the formulation of a series of actions to eliminate the waste.…”
Section: Introductionmentioning
confidence: 99%